Operant down-conditioning of the soleus H-reflex in people after stroke - Thompson, Aiko K.; Gill, Christina R.; Feng, Wuwei; Segal, Richard L. (Frontiers in Rehabilitation Sciences, 2022)
Through operant conditioning, spinal reflex behaviors can be changed. Previous studies in rats indicate that the sensorimotor cortex and corticospinal tract are essential in inducing and maintaining reflex changes induced through conditioning. In people with incomplete spinal cord injury (SCI), an operant down-conditioning protocol decreased the soleus H-reflex size and improved walking speed and symmetry, suggesting that a partially preserved spinal cord can support conditioning-induced plasticity and benefit from it. This study examined whether down-conditioning can decrease the soleus H-reflex in people with supraspinal injury (i.e., cortical or subcortical stroke). Operant down-conditioning was applied to the soleus H-reflex in a cohort of 12 stroke people with chronic spastic hemiparesis (>12 months from stroke onset of symptoms). Each participant completed 6 baseline and 30 conditioning sessions over 12 weeks. In each baseline session, 225 control H-reflexes were elicited without any feedback on H-reflex size. In each conditioning session, 225 conditioned H-reflexes were elicited while the participant was asked to decrease H-reflex size and was given visual feedback as to whether the resulting H-reflex was smaller than a criterion value. In six of 12 participants, the conditioned H-reflex became significantly smaller by 30% on average, whereas in other 6 participants, it did not. The difference between the subgroups was largely attributable to the difference in across-session control reflex change. Ten-meter walking speed was increased by various extent (+0.04 to +0.35, +0.14 m/s on average) among the six participants whose H-reflex decreased, whereas the change was 0.00 m/s on average for the rest of participants. Although less than what was seen in participants with SCI, the fact that conditioning succeeded in 50% of stroke participants supports the feasibility of reflex down-conditioning in people after stroke. At the same time, the difference in across-session control reflex change and conditioning success rate may reflect a critical role of supraspinal activity in producing long-term plasticity in the spinal cord, as previous animal studies suggested.